Analysis of Independence, Competence, Objectivity, and Accountability on Audit Quality (Case Study on Public Accountant Firms in Semarang City) - Nafisah, Kholifatun; Anton (AJAR, 2026)
This study aim to determine the effect of independence, competence, objectivity, and accountability on audit quality. This study used purposive sampling and distributed questionnaires to auditors at public accounting firm in Semarang. A total of 115 questionnaires were distributed, 107 were returned, and 103 met the criteria, resulting in a sample size of 103. Data analysis was performed using multiple linier regression with SPSS software. The result of this study indicate that independence, competence, and accountability have a positive and significant effect on audit quality. Meanwhile, objectivity has a positive but insignificant effect on audit quality.